2010
DOI: 10.1002/dta.155
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of second‐generation ‘legal highs’ in the UK: Initial findings

Abstract: In the UK, mephedrone and other so-called 'legal high' derivatives have recently been classified as Class B, Schedule I under the Misuse of Drugs Act 1971. Since then, alternative products have been advertised on a number of websites. In order to obtain an immediate snapshot of the situation, 24 products were purchased online from 18 UK-based websites over a period of 6 weeks following the ban in April 2010. Qualitative analyses were carried out by gas chromatography ion trap mass spectrometry using electron-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
229
3
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(241 citation statements)
references
References 17 publications
5
229
3
4
Order By: Relevance
“…It is possible that the Internet suppliers themselves may be confused as to which substance they are intending to sell, since in some user discussion fora, there appears to be confusion between 4-methylaminorex and 4,4′-dimethylaminorex [13,14]. In addition, there are numerous studies that have demonstrated that the contents of NPS products purchased from the Internet, high street headshops or street-level drug dealers are variable and the actual contents may not reflect the stated contents [15][16][17][18][19][20]. The main limitation of the Internet snapshot methodology is that the products are not purchased and analysed; therefore, it is not possible to be certain of the actual contents of the products being sold.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the Internet suppliers themselves may be confused as to which substance they are intending to sell, since in some user discussion fora, there appears to be confusion between 4-methylaminorex and 4,4′-dimethylaminorex [13,14]. In addition, there are numerous studies that have demonstrated that the contents of NPS products purchased from the Internet, high street headshops or street-level drug dealers are variable and the actual contents may not reflect the stated contents [15][16][17][18][19][20]. The main limitation of the Internet snapshot methodology is that the products are not purchased and analysed; therefore, it is not possible to be certain of the actual contents of the products being sold.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a patient population with sympathomimetic toxicity, it cannot be reliably distinguished whether caffeine contributed to the clinical manifestations of sympathomimetic toxicity or not. Furthermore, there are several reports of novel psychoactive substances, specifically those claiming to be synthetic cathinones, that were analyzed and found to contain significant concentrations of caffeine with some containing only caffeine [11][12][13].…”
Section: Limitationsmentioning
confidence: 99%
“…The illegal status of the classic psychostimulants (particularly MDMA and cocaine) has encouraged users to seek newer drugs that have become increasingly available through the Internet, which allows effective marketing, sale and distribution and is the major reason for the increase in their availability (Brandt et al, 2010;McElrath and O' Neill, 2011;Karila and Reynaud, 2010).…”
Section: Introductionmentioning
confidence: 99%